Ecological models of alcohol outlets and violent assaults: crime potentials and geospatial analysis. - Gruenewald PJ; Freisthler B; Remer L; LaScala EA; Treno A (Addiction, 2006)
AIMS: Empirical tests of relationships between alcohol outlets and violence are generally conducted with statistical controls for correlates related to characteristics of people and the places in which they live. Crime potentials theory asserts that certain subpopulations are disposed to participate in criminal activities (population potentials) and certain neighborhoods are more likely to be places where crimes occur (place potentials). The current study assesses the degree to which measures of the different geographic distributions of these potentials contribute to violent crime. DESIGN: Cross-sectional data on hospital discharges for violent assaults were obtained for residents of 1637 zip code areas in California. Assault rates were related to measures of population and place characteristics using spatial statistical models corrected for spatial autocorrelated error. FINDINGS: Rates of assault were related to population and place characteristics within zip code areas, and with characteristics of populations living in adjacent zip code areas. Assault rates were greater in densely populated, poor minority urban areas with greater residential instability. Assault rates were also greater in zip code areas adjacent to densely populated urban areas. Assault rates were related significantly to local densities of off-premise alcohol retail establishments, not bars. However, densities of bars moderated substantially effects related to local population characteristics. Bars were related significantly to violence in unstable poor minority areas and in rural middle-income areas of the state. CONCLUSION: Population and place characteristics are associated with rates of violence across spatial areas. Alcohol outlets directly affect and moderate potentials for violence associated with socio-demographic groups.